Prevalence of anterior open bite and associated factors in schoolchildren in a municipality of southern Brazil - Eliane TRAEBERT; Vinícius Freitas MARCOS; Daniela Quedi WILLIG; Jefferson TRAEBERT (Universidade Estadual Paulista, 2021)
Abstract Introduction Open bite can generate relevant psychosocial impact in the daily life of the patient, both from the aesthetic and functional point of view. Objective The aim of this study was to estimate the prevalence and factors associated with the anterior open bite in children in the first school year in a municipality in southern Brazil. Material and method A cross-sectional study was carried out with six-year-old schoolchildren in Palhoça/SC. Interviews were conducted with mothers to gather socioeconomic and non-nutritive sucking habits information. Children oral clinical examinations were carried out in schools. Multivariate analyses were performed using Poisson regression with a robust estimator. The study involved 655 children, 50.5% being female. Result The prevalence of anterior open bite was 14.1% (95% CI 11.5; 16.7). Girls exhibited a lower prevalence [PR= 0.96 (95% CI 0.94; 0.99) p= 0.024] and those children who used a pacifier exhibited a higher prevalence of anterior open bite [PR= 1.04 (95% CI 1.01; 1.07) p= 0.003]. Conclusion The prevalence was 14.1% and that it was associated with gender and the use of pacifier, in a statistically significant and independent way.